Regulation of minute virus of mice NS1 replicative functions by atypical PKCλ in vivo - Nüesch, Jürg P. F.; Rommelaere, Jean (Journal of virology, 2003)
Minute virus of mice NS1 protein is a multifunctional phosphoprotein endowed with a variety of enzymatic and regulatory activities necessary for progeny virus particle production. To regulate all of its different functions in the course of a viral infection, NS1 has been proposed to be modulated by posttranslational modifications, in particular, phosphorylation. Indeed, it was shown that the NS1 phosphorylation pattern is altered during the infectious cycle and that the biochemical profile of the protein is dependent on the phosphorylation state of the polypeptide. Moreover, in vitro approaches have identified members of the protein kinase C (PKC) family, in particular, atypical PKC, as regulators of viral DNA replication through the phosphorylation of NS1 residues T435 and S473, thereby activating the protein for DNA unwinding activities. In order to substantiate these findings in vivo, we produced NS1 in the presence of a dominant-negative PKCλ mutant and characterized the purified protein in vitro. The NS1 protein produced under these conditions was found to be only partially phosphorylated and as a consequence to be deficient for viral DNA replication. However, it could be rescued for this viral function by treatment with recombinant activated PKCλ. Our data clearly demonstrate that NS1 is a target for PKCλ phosphorylation in vivo and that this modification is essential for the helicase activity of the viral polypeptide. In addition, the phosphorylation of NS1 at residues T435 and S473 appeared to occur mainly in the nucleus, providing further evidence for the involvement of PKCλ which, unlike PKCζ, accumulates in the nuclear compartment of infected cells.
Gesehen am 18.02.2021